Volume 3A: Coal, Biomass and Alternative Fuels; Cycle Innovations; Electric Power; Industrial and Cogeneration 2014
DOI: 10.1115/gt2014-27121
|View full text |Cite
|
Sign up to set email alerts
|

Performance Improvement of Gas Turbine With Compressed Air Injection for Low Density Operational Conditions

Abstract: Gas Turbines are an important contributor to the world’s power generation at base and peak load conditions, and this participation is expected to last for the decades to come, even with the increasing use of renewable energies given their unique ability to supply large amounts of power in a short period of time (unlike coal or nuclear plants). On the other hand, the power produced by gas turbines is significantly reduced at higher ambient temperatures, which coincides with the peak power demand. Air density is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It also shows that the surge limit can be reached through air injection and can vary depending on the compressor design. In the analytical work by Quintero et al [2], air injection was deployed at lower density conditions, to restore a GT power through compressed air injection. The works of Abudu et al [3,5] shows an analytical engine-level analysis of air injection behind the compressor, for heavyduty GT and aero-derivative engines respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also shows that the surge limit can be reached through air injection and can vary depending on the compressor design. In the analytical work by Quintero et al [2], air injection was deployed at lower density conditions, to restore a GT power through compressed air injection. The works of Abudu et al [3,5] shows an analytical engine-level analysis of air injection behind the compressor, for heavyduty GT and aero-derivative engines respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The CAES system provides stored higher-pressure air than that of the GT maximum, to allow for air injection for power output augmentation or ramp-up rate increase. Existing research specifically on GT air injection includes [1][2][3] that covers power augmentation, and [3][4][5] that addresses the improvement of engine ramp-up rates. The previous study by Igie et al 1 indicated that it is possible to elevate the GT power output by 36% through 17.5% air injection at the back of the compressor, keeping the combustor outlet temperature (COT) fixed.…”
Section: Introductionmentioning
confidence: 99%
“…Internal combustion engines are less sensitive to temperature and humidity, maintaining their nominal power output and efficiency over a broader range of ambient conditions. Hence, some companies designed a series of standardized building block modules which can be connected together to operate at high injection air flows [10]. Combined diesel-engine gas turbine systems enable distributed power generation plants to attain high thermal efficiencies while enjoying the operational advantages of both diesel engines and gas turbines [11].…”
Section: Introductionmentioning
confidence: 99%